(untitled) (Foro de Educacion, 2024)
Since the last two decades of the twentieth century, in a wide range of countries, In debates concerning education policies, a topic of frequent approach is the influence that international institutions engage towards convergence of policies and types of organization and regulation of education. Portugal, identifying also with this international context and integrating it, has promoted policies that embrace the benchmarks of that context, in particular by adopting models of management which are sustained in logics of decentralization and of reinforcement of the autonomy of schools. Several ideological streams have been present at all stages of the process called Strengthening the Autonomy of Schools, which drag for almost twenty years. Speeches and practices to promote the rationalization of resources, promoting the effectiveness and efficiency of education, as well as the accountability, gain special evidence, under pressure from unsatisfactory results achieved by the country in international compara- tive studies and reports. Give more power and greater capacity for decision –more autonomy– in schools remains the aim of the government action. Evaluation and accountability, in that context, are, then, simultaneously, factors and instruments of policy options and condition for more autonomy to schools.